Using methods of substitution solve the following simultaneous equations: y - 2x - 1 = 0 and 4x^2 + y^2 - 25 = 0

(1) 4x2 + y2 - 25 = 0 (2) y - 2x - 1 = 0
Rearranging (2) into an equation of y in terms of x we have:y = 2x +1
now substituting into equation (1) 4x2 + (2x +1)2 - 25 = 0 and now expanding this equation we have,
4x2 + (4x2 + 4x + 1) - 25 = 0 Expanding out the brackets8x2 +4x + 1 - 25 = 0 here we simplify the equation8x2 + 4x - 24 = 0 dividing through by 4 gives us,2x2 + x - 6 = 0
Now we factorise to find out our x values:(2x -3)(x+2)= 0Our x values are therefore x = -2 and x = 3/2
Now we substitute back into equation (2)our y values are then y = 4 and y = -3




Answered by Kerry M. Maths tutor

3035 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the total area enclosed between y = x^3 - x, the x axis and the lines x = 1 and x= -1 . (Why do i get 0 as an answer?)


What is an easy way to remember how sin(x) and cos(x) are differentiated and integrated?


Express (5sqrt(3)-6)/(2sqrt(3)+3) in the form m+nsqrt(3) where m and n are integers. [Core 1]


Find the gradient of the line Y = X^3 + X + 6 when X = 4


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences